Chemoprotective activity of aqueous leaf extract of Acalypha wilkesiana against cyclophosphamide-induced toxicity in rats - Chinedu P Anokwuru; God’swill N Anyasor; Olutayo S Shokunbi; Babajide Sopekan; Oyindamola K Osinuga; Olusola E Afolabi; Olamide B Arojojoye; Chibundu N Ezekiel; Isaiah DI. Ramaite (Asian Pacific Journal of Tropical Medicine, 2019)
Objective: To investigate the protective effect of aqueous leaf extract of Acalypha (A.) wilkesiana Muell. Arg (Euphorbiaceae) against cyclophosphamide-induced toxicity in albino rats. Methods: Twenty male albino rats were randomly divided into five groups of four animals each. The control group (I) was fed with pellets and distilled water, while group II was orally administered with only 20 mg/kg cyclophosphamide. Groups III, IV and V were co- administered with 20 mg/kg body weight cyclophosphamide and 110, 220 and 440 mg/kg body weight A. wilkesiana leaf extract, respectively, for 7 d. After treatment, liver and kidney function biomarkers, haematological parameters, liver antioxidants, and mitochondrial membrane permeability transition pore opening were investigated. Results: A. wilkesiana leaf extract significantly reduced (P<0.05) cyclophosphamide-induced increase in plasma aspartate aminotransferase, alanine aminotransferase, creatinine, uric acid and urea. It increased superoxide dismutase, catalase, glutathione-S-transferase activities and reduced glutathione levels. It also increased packed cell volume count, hemoglobin concentration and white blood cell count while inhibiting the induction of mitochondrial swelling. Conclusions: This study demonstrates that aqueous extract of A. wilkesiana leaf protected tissues against cyclophosphamide-induced oxidative damage.